Social Media Platforms for Electrochemistry. (December 2019) - Khoo, Edwin; Lacey, Matthew J.; DeCaluwe, Steven C.
Abstract : While social media is increasingly used for social interaction and information dissemination, it remains underused by researchers for professional development and networking (science inreach) and science communication (science outreach). This situation is unfortunate because social media can offer a more frictionless way of interacting with other researchers and the general public compared to traditional communication tools such as email.